Intrauterine plasma treatment for endometritis in Jersey crossbred cows - METHAI, A; RAJASUNDARAM, R C; VEERAPANDIAN, C; AHMAD, MUSHTAQ (The Indian Journal of Animal Reproduction, 2023)
Intrauterine therapy with autologous plasma was evaluated for its therapeutic efficiency in cross bred Jersey cows with endometritis. Eight cows with endometritis were given intrauterine infusion of 50 ml autologous plasma on day 1, 2 and 3 of oestrous cycle considering day of estrus as day 0. The cows were evaluated in terms of physico-chemical characteristics of estrual mucus (viz., pH, nature of estrual mucus and white side test), histopathology of uterine biopsy and conception rate. The treated cows showed improvement in all the above parameters mentioned and conception rate was 50%. Hence, the intrauterine autologous plasma treatment recovers cross bred Jersey cows from endometritis.